Pengaruh Stres Akademik dan Self-Compassion terhadap Perilaku Prososial pada Mahasiswa Fakultas Teknik di Universitas Negeri Padang - Nurhidayah, Asyifa; Mardianto, Mardianto (Lembaga Yasin AlSys, 2025)
Prosocial behavior among university students in academic settings is influenced by various psychological factors, including academic stress and self-compassion. This study aims to analyze the influence of academic stress and self-compassion on prosocial behavior among students of the Faculty of Engineering at Universitas Negeri Padang. Employing a quantitative approach with a survey method, the study involved 108 students selected through stratified sampling. Instruments included scales measuring academic stress, self-compassion, and prosocial behavior. Data were analyzed using multiple linear regression to determine the contribution of each variable to prosocial behavior. The results indicate that academic stress and self-compassion jointly have a significant effect on prosocial behavior. Partially, academic stress has a significant negative effect, while self-compassion has a significant positive effect on prosocial behavior. The coefficient of determination (R²) of 0.771 indicates that 77.1% of the variation in prosocial behavior can be explained by these two independent variables. These findings highlight the importance of stress management and the cultivation of self-compassion as strategies to enhance students’ propensity for prosocial behavior in higher education environments.